Continuous Spatial Sequences of Lichen Sclerosus, Penile Intraepithelial Neoplasia, and Invasive Carcinomas: A Study of 109 Cases. (August 2019) - Cañete-Portillo, Sofía; Sanchez, Diego F.; Fernández-Nestosa, María José; Piris, Adriano; Zarza, Patricia; Oneto, Sabrina; Gonzalez Stark, Lorena; Lezcano, Cecilia; Ayala, Gustavo; Rodriguez, Ingrid; Hoang, Mai P.; Mihm, Martin C.; et al.
Lichen sclerosus (LSc) with penile cancer is found in about two thirds of specimens. It has been hypothesized that LSc represents a precancerous condition. To qualify as such, in addition to cytological atypia and similarity with the invasive tumor, a spatial correlation between LSc and neoplastic lesions needs to be demonstrated. The purpose of this study was to evaluate such a spatial relationship. Circumcision (28 cases) and penectomy (81 cases) specimens were evaluated. All cases had LSc, penile intraepithelial neoplasia (PeIN), and/or invasive squamous cell carcinomas. We examined LSc in relation to invasive carcinoma, PeIN, and normal epithelia. Invasive squamous cell carcinomas, classified according to the World Health Organization criteria as non–human papillomavirus (HPV)-related and HPV-related PeIN, were present in 100 cases. Non-HPV-related (differentiated) PeIN was the most common subtype associated with LSc (89%). There were 5 spatial patterns identified: (1) LSc adjacent to PeIN (23%), (2) LSc adjacent and comprising PeIN (42%), (3) LSc next to and within invasive carcinomas (8%), (4) LSc throughout the sequence PeIN-invasive carcinoma (24%), and (5) LSc was separate (with normal tissue between the lesions) from PeIN and/or invasive carcinomas in a minority of cases (3%). LSc within the cancer was not previously described. In this series, we found 35 cases with LSc within invasive carcinomas. The striking continuous spatial relationship among LSc, PeIN, and/or invasive carcinoma as shown in this study may be a necessary (but not sufficient) condition for the hypothesis postulating LSc as a penile precancerous lesion.